Level of NICU Quality of Developmental Care and Neurobehavioral Performance in Very Preterm Infants - Rosario Montirosso; Alberto Del Prete; Roberto Bellù; Ed Tronick; Renato Borgatti (2012)
To examine the relation between the neurobehavior of very preterm infants and the level of NICU quality of developmental care.The neurobehavior of 178 very preterm infants (gestational age ≤29 weeks and/or birth weight ≤1500 g) from 25 NICUs participating in a large multicenter, longitudinal study (Neonatal Adequate Care for Quality of Life, NEO-ACQUA) was examined with a standardized neurobehavioral assessment, the NICU Network Neurobehavioral Scale (NNNS). A questionnaire, the NEO-ACQUA Quality of Care Checklist was used to evaluate the level of developmental care in each of the NICUs. A factor analyses applied to NEO-ACQUA Quality of Care Checklist produced 2 main factors: (1) the infant-centered care (ICC) index, which measures parents' involvement in the care of their infant and other developmentally oriented care interventions, and (2) the infant pain management (IPM) index, which measures the NICU approach to and the procedures used for reducing infant pain. The relations between NNNS neurobehavioral scores and the 2 indexes were evaluated.Infants from NICUs with high scores on the ICC evidenced higher attention and regulation, less excitability and hypotonicity, and lower stress/abstinence NNNS scores than infants from low-care units. Infants from NICUs with high scores on the IPM evidenced higher attention and arousal, lower lethargy and nonoptimal reflexes NNNS scores than preterm infants from low-scoring NICUs.Very preterm infant neurobehavior was associated with higher levels of developmental care both in ICC and in IPM, suggesting that these practices support better neurobehavioral stability.